Phenotypic and genotypic characterization of antimicrobial resistant Escherichia coli isolated from ready-to-eat food in Singapore using disk diffusion, broth microdilution and whole genome sequencing methods - Guo, Siyao (2021)
This study aimed to determine the antimicrobial resistance (AMR) profiles of Escherichia coli isolated from ready-to-eat (RTE) food sold in retail food premises in Singapore. In this study, a total of 99 E. coli isolates from poultry-based dishes (n = 77) and fish-based dishes (n = 22), obtained between 2009 and 2014, were included for disk diffusion testing. Of the 99 isolates, 24 (24.2%) were resistant to at least one antimicrobial agent. These isolates were then subjected to broth microdilution testing against 33 antimicrobial agents, including beta-lactams, aminoglycosides, tetracycline, fluoroquinolones and polymyxin E (also known as colistin) to determine the minimum inhibitory concentration (MIC) of isolates. Finally, whole genome sequence (WGS) was carried out on the strains in order to correlate resistant phenotypes to putative antimicrobial-related genes. Of the 24 isolates, 15 (62.5%) were found to be resistant to three or more classes of antimicrobials and thus were defined as multidrug resistant strains. Two isolates (8.3%) were confirmed as Extended-Spectrum Beta-Lactamase (ESBL)-producing E. coli by double-disk synergy test. Based on WGS data, online analysis tool ResFinder detected 7 classes of AMR genes and resistance-related chromosomal point mutations in 19 of the 24 E. coli isolates. Prediction of AMR using WGS data was evaluated for six antimicrobials including ampicillin, chloramphenicol, colistin, fluoroquinolones, tetracycline and trimethoprim. By analyzing the WGS contigs using BLASTn and KmerFinder, quinolone resistance genes, ESBL genes and transferable colistin resistance gene mcr-1 and mcr-5 were determined to be located on plasmids, which could pose a greater risk of AMR transfer among bacteria. Mutations were detected in four isolates within genes previously shown to confer resistance to quinolones (gyrA and parE) and tetracycline (rrsB). This study showed the presence of AMR E. coli isolates in RTE food, and raises a concern on the possible transmission of AMR bacteria from food to humans.